A Migratory Divide Among Red-Necked Phalaropes in the Western Palearctic Reveals Contrasting Migration and Wintering Movement Strategies - van Bemmelen, Rob S. A.; Kolbeinsson, Yann; Ramos, Raül; Gilg, Olivier; Alves, José A.; Smith, Malcolm; Schekkerman, Hans; Lehikoinen, Aleksi; Petersen, Ib Krag; Þórisson, Böðvar; Sokolov, Aleksandr A.; Välimäki, Kaisa; et al. (Frontiers in Ecology and Evolution, 2019)
Non-breeding movement strategies of migratory birds may be expected to be flexibly adjusted to the distribution and quality of habitat, but only few studies compare movement strategies between populations using distinct migration routes and wintering areas. In thisour study, individual movement strategies of Rred-necked pPhalaropes Phalaropus lobatus, a long-distance migratory wader using saline waters in the non-breeding period, were studied using light-level geolocators. Results revealed the existence of two populations with distinct migration routes and wintering areas: one breeding in the north-eastern North Atlantic and migrating ca. 10,000 km oversea to the tropical eastern Pacific Ocean and the other breeding in Fennoscandia and Russia migrating ca. 6,000 km – largely over land – to the Arabian Sea (Indian Ocean). In line with our expectations, the transoceanic migration between the North Atlantic and the Pacific was associated with proportionately longer wings, a more even spread of stopovers in autumn and a higher migration speed in spring compared to the migration between Fennoscandian-Russian breeding grounds and the Arabian Sea. In the wintering period, birds wintering in the Pacific were stationaryresided in roughly a singlethe same area, whereas individuals wintering in the Arabian Sea showed individually consistent movementsd extensively between different areas, reflecting differences in spatio-temporal variation in primary productivity between the two wintering areas. Our study is unique in showing how habitat distribution shapes movement strategies over the entire non-breeding period within a species.